Proceedings of the Fourth International Conference on SImilarity Search and APplications 2011
DOI: 10.1145/1995412.1995417
|View full text |Cite
|
Sign up to set email alerts
|

Ptolemaic indexing of the signature quadratic form distance

Abstract: The signature quadratic form distance has been introduced as an adaptive similarity measure coping with flexible content representations of multimedia data. While this distance has shown high retrieval quality, its high computational complexity underscores the need for efficient search methods. Recent research has shown that a huge improvement in search efficiency is achieved when using metric indexing. In this paper, we analyze the applicability of Ptolemaic indexing to the signature quadratic form distance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…The similarity function f s is used to determine similarity values between all pairs of representatives from the feature signatures. In our implementation we use the similarity function f s (r i , r j ) = e −αL 2 (r i ,r j ) 2 , where α is a constant for controlling the precision-indexability tradeoff, as investigated in our previous works [1,19], and L 2 denotes the Euclidean distance. In particular, lower values of the parameter α lead to better indexability, that is, to a smaller intrinsic dimensionality (iDIM) [8].…”
Section: Definition 1 (Sqfd) Given Two Feature Signaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The similarity function f s is used to determine similarity values between all pairs of representatives from the feature signatures. In our implementation we use the similarity function f s (r i , r j ) = e −αL 2 (r i ,r j ) 2 , where α is a constant for controlling the precision-indexability tradeoff, as investigated in our previous works [1,19], and L 2 denotes the Euclidean distance. In particular, lower values of the parameter α lead to better indexability, that is, to a smaller intrinsic dimensionality (iDIM) [8].…”
Section: Definition 1 (Sqfd) Given Two Feature Signaturesmentioning
confidence: 99%
“…Nevertheless, recent papers showed that SQFD can be indexed by metric access methods [1] and ptolemaic indexing [19], achieving a speed-up of up to two orders of magnitude with respect to the sequential scan. In this section we review both approaches and detail the simplest and most intuitive metric/ptolemaic index: the pivot tables.…”
Section: Indexingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, w q = (w The similarity function f s is used to determine similarity values between all pairs of representatives from the feature signatures. In our implementation, we use the similarity function f s (r i , r j ) = e −αL2(ri,rj ) 2 , where α is a constant for controlling the precision-indexability tradeoff, as investigated in previous works [4,19], and L 2 denotes the Euclidean distance. In particular, the lower values of α lead to better indexability (allowing fast search), that is, to lower values of so-called intrinsic dimensionality (iDIM) [8].…”
Section: Definition 1 (Sqfd) Given Two Feature Signaturesmentioning
confidence: 99%
“…Nevertheless, recent papers showed that SQFD can be indexed by metric access methods [4] and ptolemaic indexing [19], achieving a speed-up of up to two orders of magnitude with respect to the sequential scan.…”
Section: Efficiency Of the Retrievalmentioning
confidence: 99%